1990
DOI: 10.1056/nejm199004263221703
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Acute Graft Rejection by the Prostaglandin E1Analogue Misoprostol in Renal-Transplant Recipients Treated with Cyclosporine and Prednisone

Abstract: Prostaglandins of the E series have been shown to have immunosuppressive properties. To study the effects of the prostaglandin E1 analogue misoprostol on renal function and graft rejection after transplantation, we conducted a randomized, double-blind, placebo-controlled trial in 77 renal-allograft recipients. The subjects received misoprostol (200 micrograms four times daily by mouth; n = 38) or placebo (n = 39) for the first 12 weeks after transplantation, in addition to standard immunosuppression with cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…In rats, it was shown that prostaglandin E2 reduces nephrotoxicity of cyclosporine, but this was likely mediated by an interaction between prostaglandin E2 and intestinal cyclosporine absorption (368). Misoprostol, a prostaglandin E1 analog, reduced CNI nephrotoxicity in vitro and in rats treated with chronic cyclosporine (369,370), and in a human study, misoprostol was shown to improve renal function (371). This effect in humans was, however, associated with a lower incidence of acute rejection with misoprostol treatment, misoprostol in itself did not prevent the development of CNI nephrotoxicity in humans (371).…”
Section: Other Approachesmentioning
confidence: 92%
See 1 more Smart Citation
“…In rats, it was shown that prostaglandin E2 reduces nephrotoxicity of cyclosporine, but this was likely mediated by an interaction between prostaglandin E2 and intestinal cyclosporine absorption (368). Misoprostol, a prostaglandin E1 analog, reduced CNI nephrotoxicity in vitro and in rats treated with chronic cyclosporine (369,370), and in a human study, misoprostol was shown to improve renal function (371). This effect in humans was, however, associated with a lower incidence of acute rejection with misoprostol treatment, misoprostol in itself did not prevent the development of CNI nephrotoxicity in humans (371).…”
Section: Other Approachesmentioning
confidence: 92%
“…Misoprostol, a prostaglandin E1 analog, reduced CNI nephrotoxicity in vitro and in rats treated with chronic cyclosporine (369,370), and in a human study, misoprostol was shown to improve renal function (371). This effect in humans was, however, associated with a lower incidence of acute rejection with misoprostol treatment, misoprostol in itself did not prevent the development of CNI nephrotoxicity in humans (371). Likewise, another study in patients with rheumatoid arthritis did not observe any effect of misoprostol treatment on acute CNI nephrotoxicity (372).…”
Section: Other Approachesmentioning
confidence: 99%
“…[6][7][8] We now describe a baboon-to-human liver xenotransplantation in which FK 506 and cyclophosphamide were given as immunosuppressants, together with prednisone and prostaglandin, both of which help to mitigate preformed antigraft antibody syndromes and cellular rejection. 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Suggested regimens include OKT3 induction in combination with azathioprine and steroids, with or without low doses of calcineurin inhibitors. [4][5][6] A new option in this circumstance is the use of daclizumab with mycophenolate mofetil (MMF) and steroids.…”
mentioning
confidence: 99%